2020
DOI: 10.1038/s41598-020-60169-1
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeological evidence of the AD 1642 Yellow River flood that destroyed Kaifeng, a former capital of dynastic China

Abstract: Rising global temperatures will increase the number of extreme weather events, creating new challenges for cities around the world. Archaeological research on the destruction and subsequent reoccupation of ancient cities has the potential to reveal geological and social dynamics that have historically contributed to making urban settings resilient to these extreme weather events. Using a combination of archaeological and geological methods, we examine how extreme flood events at Kaifeng, a former capital of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…However, as one of the most active fluvial landforms that are profoundly affected by volatile hydrodynamic and sedimentation regimes, floodplains also produce highly complex environmental records (Boyer et al, 2006; A. Brown, 1997; A. G. Brown, 2002; T. Brown, 2002; Ferring, 2001; Howard & Macklin, 1999; Li et al, 2021; Nanson & Croke, 1992; Storozum et al, 2020). Unpacking the relationship between the evolution of floodplain environments and the history of human occupation therefore faces enormous challenges resulting from the intrinsic complexity of environmental processes and data abstraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, as one of the most active fluvial landforms that are profoundly affected by volatile hydrodynamic and sedimentation regimes, floodplains also produce highly complex environmental records (Boyer et al, 2006; A. Brown, 1997; A. G. Brown, 2002; T. Brown, 2002; Ferring, 2001; Howard & Macklin, 1999; Li et al, 2021; Nanson & Croke, 1992; Storozum et al, 2020). Unpacking the relationship between the evolution of floodplain environments and the history of human occupation therefore faces enormous challenges resulting from the intrinsic complexity of environmental processes and data abstraction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have endeavored to disentangle the complex relationship between floods and the society based on excavated environmental records. Storozum et al (2020) reported the geoarchaeological evidence of the flood that took place in 1642 AD and its devasting impact on the Kaifeng City. Wu, Liu, Ma et al (2019) also analyzed historical documents of this massive flood.…”
Section: Regional Settingmentioning
confidence: 99%
“…After this disaster, the city was abandoned until 1662, when it was rebuilt under the rule of the Kangxi Emperor in the Qing dynasty. Archaeological research in the city has provided evidence for the 1642 flood and subsequent occupation in 1662 [52]. It remained a rural backwater city of diminished importance thereafter and experienced several other less devastating floods.…”
Section: Water Conflicts In Early and Mid-modern Times (Ca 1400-1900 Ad)mentioning
confidence: 99%